2021
DOI: 10.1097/jom.0000000000002403
|View full text |Cite
|
Sign up to set email alerts
|

Not Quite Out of the Woods

Abstract: While logging is recognized as one of the most dangerous occupations in the United States, we discovered that cardiovascular risk factors, especially hypertension and obesity are a growing concern among logging equipment operators. Improving modifiable cardiovascular risk factors among loggers should be a priority for this industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…They were also invited to participate in a one‐time, in‐person health assessment. Results from the health assessment substudy have also been previously reported 15 …”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…They were also invited to participate in a one‐time, in‐person health assessment. Results from the health assessment substudy have also been previously reported 15 …”
Section: Methodsmentioning
confidence: 84%
“…Results from the health assessment substudy have also been previously reported. 15 The survey modules can be seen in Table 1. Surveys were (1) mailed out every 3 months in paper format, (2) shared electronically using a REDCap 16,17 link via email or text message, or (3) collected through a phone call with the participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation